2019
DOI: 10.5812/ijp.84798
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Vitamin D in the Umbilical Cord of Survived with Not Survived Premature Infants

Abstract: Background: Vitamin D deficiency is associated with prematurity, respiratory problems and infections. These are important causes of death in premature neonates. Objectives: The aim of this study was to compare the vitamin D level in the blood of preterm live neonates discharged with those neonates who did not survive. Methods: In a cross-sectional study, 335 premature infants (less than 34 weeks of gestation) were discharged and 48 infants died. We examined their umbilical cord blood for vitamin D. Results: Ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The results of a study showed vitamin D deficiency was more pronounced in newborns who died. Vitamin D deficiency may increase the likelihood of death of these infants by increasing respiratory problems and infections [7].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study showed vitamin D deficiency was more pronounced in newborns who died. Vitamin D deficiency may increase the likelihood of death of these infants by increasing respiratory problems and infections [7].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of vitamin D deficiency has been reported at 30% to 88% in infants as well as mothers worldwide. [20][21][22][23][24][25][26] In a study in Iran, 552 mothers and infants were examined for serum vitamin D levels and the results showed that 66% of the mothers and 93% of the newborns had vitamin D deficiency. 27 Our findings demonstrated a high prevalence of vitamin D deficiency among Iranian mothers and newborns, which is consistent with the mentioned study.…”
Section: Discussionmentioning
confidence: 99%
“…Levels less than 10 ng/mL were considered as severe, 10 to 20 ng/mL as moderate and 20 to 30 ng/mL as mild deficiency. 23 After collecting data and entering data into SPSS version 23, tables, figures, and statistical indices were used to analyze the results and evaluate the relationship between variables. For this purpose, after checking the normal distribution of data, Pearson's correlation coefficient and independent t test were used for normally distributed data.…”
Section: Methodsmentioning
confidence: 99%
“…This is an open-access article distributed under the terms of the Creative Commons Attribution-NonCommercial 4.0 International License (http://creativecommons.org/licenses/by-nc/4.0/) which permits copy and redistribute the material just in noncommercial usages, provided the original work is properly cited. thy (21,22).…”
Section: Introductionmentioning
confidence: 99%